Analisis Teknik Facial Expression oleh Animator 3D: Studi Kasus Proyek Animasi X - Taufiqurrahman, Adhitya; Rahmi, Anis (Politeknik Negeri Batam, 2025)
The rapid development of 3D animation highlights the importance of realistic facial expressions for non-verbal communication and narrative emotion, making it necessary to research urgent shot handling techniques on relevant facial expressions. However, the production is often hampered due to technical challenges, such as the X Animation Project at PT Kinema Systrans requires special handling related to urgent shot handling techniques that require detailed notes and uniformity of facial expression handling by animators. This research uses an art-based research method with a qualitative approach that analyzes the results of urgent shot notes on the facial rig model free character Mr. Vincent. Based on the findings of the urgent shot notes, there are various terms that need to be addressed in facial expression problems. These notes indicate specific areas that need to be improved in the workflow of making facial expressions.